2005
DOI: 10.1002/bem.20132
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic field influence on electrical properties of human blood measured by impedance spectroscopy

Abstract: The impedance spectroscopy technique (IST) was used for studying the effect of a 0.5 T magnetic field on the electrical properties of whole human blood. A Solartron SI 1260 spectrometer was used to measure the impedance spectra of magnetic field exposed blood samples compared to non-exposed samples. An equivalent electrical circuit model, consisting in a resistance Rs in series with a parallel circuit formed by a constant phase element (CPE) and another resistance Rp, is proposed to fit the data in both cases.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 27 publications
1
7
0
1
Order By: Relevance
“…The literature has reported an increased blood resistance when it is exposed to static MF [6], in this work similar effect is shown using AMF.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…The literature has reported an increased blood resistance when it is exposed to static MF [6], in this work similar effect is shown using AMF.…”
Section: Resultssupporting
confidence: 82%
“…Blood cells have also been studied, in particular, Higashi et al (1997) [5] studied the orientation of erythrocytes under a static MF of 8.0 T where a parallel orientation to the field lines was observed, authors suggested that this is due to magnetic features of the cell membrane. Later, M. Sosa et al (2005) [6] studied the changes in the electrical properties of the blood when it was exposed to a magnetic field of 0.5 T finding a resistance increase of 10.4 % and a 1.9 % in capacitance; given the highly non-conductive membrane properties, they were able to explain these * email: theo@dci.ugto.mx changes based on ion currents induced in the interstitial medium and the charge distribution generated in the membrane surface because of ions that remain attached to it. Other authors have studied sedimentation and aggregation behavior when the erythrocytes are in a MF of the order of 6.0 T [7].…”
mentioning
confidence: 97%
“…However, there may be other transduction pathways through which EMF signals could modulate tissue repair and growth. For example, several recent studies have reported EMF effects on human Hb in solution and erythrocyte suspensions, including decreases in viscosity [7] and changes in impedance [8], dielectric properties [9], dia- and para-magnetic properties [10], optical absorption [11] and in vivo deoxygenation [12]. In addition, radiofrequency mobile telephone signals have been shown to decrease Hb oxygen affinity in vitro [13] and changes in infrared absorption have been reported for low-frequency EMF [14].…”
Section: Introductionmentioning
confidence: 99%
“…Electrical impedance spectroscopy (EIS) has proven useful in the characterization of biomaterials by recording the behavior of their intrinsic properties while evaluating the bioelectrical response of the system as a sinusoidal excitation signal is applied [9]. It has also been used to measure biological tissues in which the electrical impedance depends on water content and ionic conduction in the body.…”
Section: Introductionmentioning
confidence: 99%